2019
DOI: 10.1891/1052-3073.30.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Risk Tolerance and the Financial Satisfaction of Credit Card Users

Abstract: This study tests whether risk tolerance mitigates the effects of credit card mismanagement on users' financial satisfaction. We used data from the Health and Retirement Study and found results showing that credit card mismanagement reduces the financial satisfaction of lower-risk-tolerance users only. The results also suggest that the psychic costs of credit card mismanagement (i.e., stress and anxiety), not the monetary costs (fees and higher interest rates), may be the biggest contributors to the dissatisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The study found that the credit card debt of college students adversely affected their FWB and recommended a few research directions using the CARD Act. Further, the stress and anxiety incurred during credit card mismanagement can lower FWB for low risk‐tolerance consumers (desirable income and the possibility of financial loss) (Payne et al., 2019).…”
Section: An Organizing Framework Of Research Gaps In Financial Well‐beingmentioning
confidence: 99%
“…The study found that the credit card debt of college students adversely affected their FWB and recommended a few research directions using the CARD Act. Further, the stress and anxiety incurred during credit card mismanagement can lower FWB for low risk‐tolerance consumers (desirable income and the possibility of financial loss) (Payne et al., 2019).…”
Section: An Organizing Framework Of Research Gaps In Financial Well‐beingmentioning
confidence: 99%
“…Contrary to this, few others support a positive relationship between risk tolerance and financial satisfaction contending that more risk tolerant individuals perform positive financial behaviors and in turn, are highly satisfied (Castro et al 2020 ). Credit card users with a high tolerance for risk are also found to be more financially satisfied than low risk tolerant users (Payne et al 2019 ).…”
Section: Literature Review Of Key Enablers Selected For the Studymentioning
confidence: 99%
“…As risk tolerance is determined by an individual's financial knowledge, education, and income, an individual with high risk tolerance performs positive financial behaviours which bring them closer to financial satisfaction (Payne et al . 2019). Financial self‐efficacy, which represents an individual's judgment of their own ability to execute desirable actions, is also a significant component in increasing FWB (Gutter and Copur 2011; Limbu and Sato 2019).…”
Section: Content Analysismentioning
confidence: 99%